2010
DOI: 10.3382/ps.2009-00328
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial clearance, heterophil function, and hematological parameters of transport-stressed turkey poults supplemented with dietary yeast extract

Abstract: Yeast extracts (YE) contain biological response modifiers that may be useful as alternatives to antibiotics for controlling pathogens in poultry production and mitigating the deleterious effects of production stressors. The objective of the present study was to determine the ability of a commercial dietary YE (Alphamune) to modulate the immune response in male turkey poults challenged with Escherichia coli and subjected to transport stress. Alphamune was added to turkey poult diets at 0, 500, or 1,000 g/ton. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 60 publications
(58 reference statements)
4
26
0
Order By: Relevance
“…We found an increase in the heterophil to lymphocyte ratios in Eimeria-challenged birds fed 0.02% bglucan (Cox et al, unpublished data). Treatment of turkey poults with a yeast extract containing bglucans resulted in similar findings where the percentage of heterophils and their oxidative burst activity was increased (Huff et al, 2010). Accordingly, the heterophil to lymphocyte ratios were also increased (Huff et al, 2007(Huff et al, , 2010.…”
Section: Effects Of B-glucans On the Innate Immune Responsesupporting
confidence: 74%
See 2 more Smart Citations
“…We found an increase in the heterophil to lymphocyte ratios in Eimeria-challenged birds fed 0.02% bglucan (Cox et al, unpublished data). Treatment of turkey poults with a yeast extract containing bglucans resulted in similar findings where the percentage of heterophils and their oxidative burst activity was increased (Huff et al, 2010). Accordingly, the heterophil to lymphocyte ratios were also increased (Huff et al, 2007(Huff et al, , 2010.…”
Section: Effects Of B-glucans On the Innate Immune Responsesupporting
confidence: 74%
“…Feed intake was again raised with the b-glucan supplemented diet. Other research laboratories, including ours, reported similar results where no deleterious effects were observed due to dietary bglucan supplementation in broilers (Cheng et al, 2004;Chen et al, 2006;Chen et al, 2008;Cox et al, 2010a,b;Morales-Lopez et al, 2009) or turkey poults (Huff et al, 2010).…”
Section: Effects Of B-glucans On Performancesupporting
confidence: 67%
See 1 more Smart Citation
“…Saccharomyces known to offer a source of good quality protein and B complex vitamins. Due to immunomodulatory properties, yeast extract, the non-antibiotic functional product is suggested to be the potential non-antibiotic alternative for decreasing pathogenic bacteria in turkey production (Huff et al, 2010). Currently, yeast cell derivatives are gaining importance as zootechnical feed additives (Świątkiewicz et al, 2014).…”
Section: Probioticsmentioning
confidence: 99%
“…It is known that the high nutrient digestibility will affect the activity of visceral organs and digestive tract, which can be measured by weight changes (Hetland et al, 2005). In addition, this will also affect the increase of erythrocyte numbers, hemoglobin and hematocrit (Huff et al, 2010), as well as stimulate the immune system to generate more antibodies (Shanmugasundaram et al, 2013). Based on this, further studies to find out the effect of feeding the local ration fermented by tape yeast with different moisture content on bird's performances need to be implemented.…”
Section: Introductionmentioning
confidence: 99%